Efficient additive manufacturing production of oxide- and nitride-dispersion-strengthened materials through atmospheric reactions in liquid metal deposition. (5th December 2016) - Springer, H.; Baron, C.; Szczepaniak, A.; Jägle, E.A.; Wilms, M.B.; Weisheit, A.; Raabe, D.
Abstract: Despite being extremely attractive compounds for strengthening, oxides and nitride particles have found only limited use in metallic materials design, as obtaining appropriate size and dispersion up to now necessitates production by time- and cost-intensive powder metallurgy processes. Here we present an alternative production method, based on the oxide and nitride formation during liquid-metal-deposition procedures in oxygen and/or nitrogen containing atmospheres. Rapid solidification of the small liquid zone suppresses floatation and agglomeration of particles, while subsequent thermo-mechanical treatments densify the material and aids particle dispersion. The in-situ particle formation coupled to the high deposition rates ensures a drastically shortened production chain. The feasibility of the method is exemplarily demonstrated on austenitic stainless steel and commercially available deposition techniques as used in additive manufacturing, performed without shielding gas but instead at air. Even without substantial optimisation of processes and material, > 2 vol.% of hard and stable Cr2 N particles with sizes down to 80 nm could be evenly dispersed, resulting in pronounced strengthening at both room temperature and 700 °C without significant loss in ductility. Future possibilities for creating novel generations of cost effective and lean high strength materials, especially for high temperature applications, are outlined and discussed. Graphical abstract: Highlights: Atmospheric reactions during liquid metal deposition for oxide and nitride particles Control of type, size and dispersion through deposition parameters, base materials and partial pressures Proof of principle resulted in formation of Cr2N and MnCrO in stainless steel Novel route for ODS and NDS materials without powder metallurgy processing